Nursing Care in Violent Behavior Disorders - Rahma, Rezta; Febriyani, Suci Melani (Yayasan Rumah Ilmu Professor, 2023)
This research aims to examine and design nursing care for two patients who are at risk of violent behavior. Observation, interviews, and analysis of patient data are data collection methods. The results showed that both patients had a history of previous violence, environmental factors, and mental health disorders. The results of the assessment can identify potential triggers, detect the level of risk, and evaluate the patient's social support and coping. The nursing diagnosis of risk disorder for violent behavior in patients underlies a treatment plan that focuses on violence prevention. Nursing intervention takes the form of self-control skills training, adaptive coping strategies, and close monitoring of behavior changes. Periodic evaluations are performed to assess the effectiveness of the treatment plan and detect changes in behavior. Discharge planning is developed by considering family support, social networks, and mental health services in the community to ensure continuity of patient care. The research concluded that nursing care for violent behavior requires a holistic approach involving interprofessional collaboration and ongoing support. Implementation of coordinated prevention strategies can help mitigate the potential for violence exhibited by patients